1997
DOI: 10.1177/000331979704800101
|View full text |Cite
|
Sign up to set email alerts
|

Local Venous Thrombosis After Cardiac Catheterization

Abstract: Pulmonary embolism is a rare but life-threatening complication of cardiac catheterization. Underlying deep venous thrombosis (DVT) is often not detectable clinically. To determine the true incidence of DVT the authors prospectively studied 450 consecutive patients (29% women, 71% men, mean age: fifty-eight years) undergoing a diagnostic cardiac catheterization. Patients were examined clinically and by duplex sonography with a high-resolution (5 or 7.5 MHz) transducer before and twenty-four hours after catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Moreover, in case with both venous and arterial puncture, the risk of developing proximal DVT is reported 3.5 times higher than arterial puncture alone. 9) Although venous thromboembolism (VTE) was incidentally recognized in this case, it is clear that keeping a high level of suspicion after the cardiac catheterization may be vital. Even if the patient has no clinical evidence of DVT after catheterization, life-threatening pulmonary embolism still can occur as in the present case.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in case with both venous and arterial puncture, the risk of developing proximal DVT is reported 3.5 times higher than arterial puncture alone. 9) Although venous thromboembolism (VTE) was incidentally recognized in this case, it is clear that keeping a high level of suspicion after the cardiac catheterization may be vital. Even if the patient has no clinical evidence of DVT after catheterization, life-threatening pulmonary embolism still can occur as in the present case.…”
Section: Discussionmentioning
confidence: 89%
“…The incidence of DVT as a complication of femoral arterial catheterization has been reported as occurring in 0.05% to 2.4% of patients. 6,7 Filis et al reported five cases of DVT in 10,450 patients who underwent femoral arterial puncture for cardiac catheterization. 7 In all five of these patients, DVT was detected after the discharge during the antiplatelet treatment and was successfully resolved using conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Most of the reported complications are bleeding, hematoma, and pseudoaneurysm. Deep-vein thrombosis (DVT) as a complication of femoral arterial catheterization has also been reported with an infrequent incidence of 0.05% to 2.4%, 6,7 and most of the reported cases were considered to have been caused by prolonged manual compression after the removal of sheath.…”
Section: Introductionmentioning
confidence: 99%
“…For our patients, femoral vein catheterization was of short duration, and most of our patients initiated de-ambulation within 4 hours; under these conditions, deep vein thrombosis rarely occurs soon after diagnostic cardiac catheterization. 2 In our experience, the femoral vein is a safe access route for endomyocardial biopsy. Its main inconvenience is the requirement for a short period of bedrest after the procedure.…”
mentioning
confidence: 87%
“…Nor have these complications been observed in other series. 2 In some reports, 3 but not others, 4 deep vein thrombosis has been associated with femoral vein catheterization in critically ill patients. For our patients, femoral vein catheterization was of short duration, and most of our patients initiated de-ambulation within 4 hours; under these conditions, deep vein thrombosis rarely occurs soon after diagnostic cardiac catheterization.…”
mentioning
confidence: 99%